Responsible technology use in tourism: Evaluating tourist guides’ digital practices through best-worst method - Cicekdagi, Munevver; Akgul, Seda Ozdemir (Journal of Tourism Management Research, 2025)
The purpose of this study is to analyze tourist guides’ awareness of responsible technology use. Conscious utilization of technology not only strengthens guides’ professional responsibilities but also enhances the quality of tourists’ experiences. It is crucial to determine how, within the guiding profession, criteria of responsible technology such as ethical awareness, data protection, sustainability, and the provision of inclusive and accessible services are prioritized. To this end, the study employs the Best-Worst Method. The findings reveal that ethical awareness and professional responsibility rank as the most significant criteria, whereas awareness of data security assumes a comparatively lower level of importance. Moreover, sustainability and accessibility solutions are identified as areas requiring greater integration by guides. The study proposes expanding ethical and digital security training in the guiding profession, increasing accessible tourism applications, and emphasizing sustainability in technology use. In doing so, it aims to promote more conscious management of digitalization in the tourism sector and contribute to its inclusiveness.